2457. Multivariate Analyses of Socio-Economic Inequities in Parental Awareness and Utilization of Meningococcal Serogroup B Vaccines. (26th November 2018) - Huang, Liping; Dempsey, Amanda; Galitsky, Alex; Fahimi, Mansour; Srivastava, Amit
Abstract: Background: In 2015, the US Advisory Committee on Immunization Practices (ACIP) made a Category B recommendation for serogroup B meningococcal (MenB) vaccines for adolescents 16–18 years. In 2016, MenB caused ~60% of invasive meningococcal disease among US individuals 16–23 years old; however, utilization of MenB vaccines was much lower than other vaccines with Category A recommendations. Therefore, we examined factors associated with awareness and utilization of MenB vaccines. Methods: An online quantitative survey was fielded among 619 US parents of adolescents aged 16–19 years, recruited from GfK's KnowledgePanel ® in December 2016. Demographics, access to care, decision making, and vaccine use were collected. A population-based weighting method was applied. Four logistic regressions and Classification And Regression Trees (CART) were conducted to examination most influential factors associated with MenB vaccine awareness and utilization. Results: Of the weighted sample, 57% were unaware of MenB vaccines (Figure 1). Results from logistic regression models (Table 1) revealed that awareness was likely associated with gender and race. Parents who obtained a recommendation from HCPs were 4.8 (95% CI: 2.5–9.4) times more likely to vaccinate or intend to vaccinate their adolescent children and 5.7 (95% CI: 2.5–12.9) times more likely have adolescents already vaccinated than those parents who did not receive the recommendation from HCP. Race/ethnicity and insurance type were associated with awareness and vaccine utilization. The results from CART verified that HCPs' recommendation is the most influential factor to predict the vaccination status. Parents' socio-economic status and their relationship with HCPs were among the most influential predictors of awareness of MenB vaccines or interest in learning about MenB vaccines if they were unaware. Conclusion: MenB awareness and vaccination are associated with parents' socio-economic status and HCPs' recommendation. Even among those unaware, there was a willingness to vaccinate when recommended by an HCP. These data underscore the critical need for robust understanding and consistent implementation of ACIP's Category B recommendation to reduce inequities in MenB vaccine awareness and utilization. Disclosures: L. Huang, Pfizer: Employee and Shareholder, Salary and Stocks. A. Dempsey, Pfizer, Merck: Scientific Advisor, Consulting fee. A. Galitsky, Pfizer: Collaborator, Research support. M. Fahimi, Pfizer: Collaborator, Research support. A. Srivastava, Pfizer: Employee and Shareholder, Salary.